Struktur Mikro, Sifat Mekanik, Dan Ketahanan Korosi Paduan Mg-Zn-Ca Yang Dihasilkan Melalui Proses Metalurgi Serbuk [Microstructure, Mechanical And Corrosion Properties of Mg-Zn-Ca Alloy via Powder Metallurgy] - Annur, Dhyah; Lestari, Franciska Pramudji; Erryani, Aprilia; Amal, M Ikhlasul; Sitorus, Lyandra S; Kartika, Ika (Jurnal Metalurgi, 2016)
Magnesium (Mg), known for its biodegradable and biocompatible properties, currently is being developed for biodegradable implant material. Unfortunately, application of Mg in biomedical devices was limited due to its low mechanical strength and low corrosion resistance. In this study, powder metallurgy was selected to process Mg-3Zn-1Ca, Mg-29Zn-1Ca, and Mg-53Zn-4.3Ca (in weight%) alloys. Holding time of sintering were varied for five and ten hours. Microstructure of Mg alloy was characterized by SEM (scanning electron microscope) and also XRD (x-ray diffraction). Compression testing was done to show the mechanical strength of Mg alloy, while corrosion resistance was examined through electrochemical testing. This study showed that ten hours of sintering time would increase mechanical properties of Mg alloy but would reduce corrosion resistance. The lowest corrosion rate was 0.32 mmpy given by Mg-29Zn-1Ca alloy and Mg-53Zn- 4Ca alloy which were sintered for five hours. Therefore, sintering time for five hours was found to be the optimum time to process Mg-Zn-Ca alloy for biodegradable implant material.